Nexmifa Regulates Axon Morphogenesis in Motor Neurons in Zebrafish - Zheng, Yu-qin; Suo, Gui-hai; Liu, Dong; Li, Hai-ying; Wu, You-jia; Ni, Hong (Frontiers in Molecular Neuroscience, 2022)
Nexmif is mainly expressed in the central nervous system (CNS) and plays important roles in cell migration, cell to cell and cell-matrix adhesion, and maintains normal synaptic formation and function. Nevertheless, it is unclear how nexmif is linked to motor neuron morphogenesis. Here, we provided in situ hybridization evidence that nexmifa (zebrafish paralog) was localized to the brain and spinal cord and acted as a vital regulator of motor neuron morphogenesis. Nexmifa deficiency in zebrafish larvae generated abnormal primary motor neuron (PMN) development, including truncated Cap axons and decreased branches in Cap axons. Importantly, RNA-sequencing showed that nexmifa-depleted zebrafish embryos caused considerable CNS related gene expression alterations. Differentially expressed genes (DEGs) were mainly involved in axon guidance and several synaptic pathways, including glutamatergic, GABAergic, dopaminergic, cholinergic, and serotonergic synapse pathways, according to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation. In particular, when compared with other pathways, DEGs were highest (84) in the axon guidance pathway, according to Organismal Systems. Efna5b, bmpr2b and sema6ba were decreased markedly in nexmifa-depleted zebrafish embryos. Moreover, both overexpression of efna5b mRNA and sema6ba mRNA could partially rescued motor neurons morphogenesis. These observations supported nexmifa as regulating axon morphogenesis of motor neurons in zebrafish. Taken together, nexmifa elicited crucial roles during motor neuron development by regulating the morphology of neuronal axons.